A Socioecological Examination of Observing Littering Behavior. Issue 3 (3rd July 2017) - Al-mosa, Yara; Parkinson, Joy; Rundle-Thiele, Sharyn
ABSTRACT: Despite evidence of the negative health, environmental, and economic impacts, littering continues to be a problem and therefore warrants ongoing research attention. Guided by a Behavioural Ecological Framework, this study observed individual-, social-, and environmental-level factors on littering behavior across three different parks in Saudi Arabia. A total of 362 individuals were observed over 12 days. Approximately half of all disposals were improper, with litter left on the ground. The most commonly littered object was nuts (29.4%). The findings revealed that environmental factors had a significant impact, including the amount of existing litter, beautification efforts, and distance to rubbish bins, and that the only significant individual factor to have any impact on individual littering behavior was group size. Implications for litter prevention are discussed. Future research opportunities are outlined.